Effect of Leadership and Work Environment on Employee Performance of Labour Office and Transmigration Sukoharjo Regency with The Motivation of Working as an Intervening - Ismanto, Ismanto (-)
The purpose of this study was to examine the effect of leadership and work environment on the performance of Dinas Tenaga Kerja dan Transmigrasi Kabupaten Sukoharjon employees. This study is the census. The data used is primary data by taking a sample of the entire population Â as many as 40 (forty-four) respondents. This study used analysis tools such as validity test, reliability test, linearity test, path analysis, multiple linear regression analysis, t test, F test and the coefficient of determination. Validity and reliability testing was done by using one-shot methods to get the results that all items are declared valid and reliable. From the linearity test results indicate that the correct model is the linear model. The results of t-test showed that the Leadership and Work Environment has a positive and significant impact on Job Satisfaction, Leadership and Work Environment has a positive but not significant effect on performance and job satisfaction has a positive and significant impact on performance. F test showed that the, Leadership and Work Environment Job Satisfaction simultaneously affect performance. The results of calculation influence directly or indirectly influence the leadership and organizational culture on employee performance shows that the direct effect of leadership and work environment on employee performance is less effective than the indirect effect. This means that both the leadership and the culture of each organization will further enhance employee performance indirectly through satisfaction. The leadersihp of the more dominant direct influence on employee performance than trought work motivation. Recommendations were submitted to management is that the Leadership Influence on employee performance through job satisfaction significantly and effectively to boost performance.Keywords : Leadership, Work Environment, Job Satisfaction, Motivation